Studying the Impact of Reading Literature on Reconstructing the Reader’s Perspective “Insights from The Writings of Ahlem Mosteghanemi and Mario Bellatin” - Boufenghour, Abir; Bouhassoun, Azzeddine (International Journal of Psychosocial Rehabilitation, 2022)
This article is an attempt to highlight the potential impact of written literary texts in reshaping the readers’ emotional rationality. The focal points of this research demonstrate the emotional mirroring that is portrayed between the readers of Ahlem Mosteghanemi and her trilogy narrators, compared to the emotional sensitivity engendered among Mario Bellatin’s readers and his creative narrators. The research paper aims at exploring the influence of these parallel emotional ties upon readers’ social parameters of reality. In this regard, some of the writers’ most challenging writings are examined according to literary analysis, constructive psychology and some scientific evaluations of theatrical studies. The findings display that reading literary works contributes effectively in reshaping the social perspective, through empowering the readers to reverse the social monitoring from a preset external level to the original individual level. Additionally, the study shows that renewing the reader’s perspective matters in updating the presentation of both the person and the society.